Comparison of the results of preimplantation genetic screening obtained by a-CGH and NGS methods from the same embryos. (30th September 2016) - Aleksandrova, N.; Shubina, E.; Ekimov, A.; Kodyleva, T.; Mukosey, I.; Makarova, N.; Kulakova, E.; Levkov, L.; Trofimov, D.; Sukhikh, G.
Abstract: Chromosomal aneuploidies are known for being the main cause of abnormal development of embryos with normal morphology, their implantation failure and early reproductive losses in IVF treatments. Preimplantation genetic screening (PGS) allows selecting embryos with normal chromosomal content and increases IVF treatment efficiency due to higher implantation rates and less frequent early pregnancy losses. New technologies used for PGS allow making genome-wide analysis of the presence of all chromosomes in embryos. This article presents our study of evaluation of two techniques used for PGS: previously developed and used in our laboratory a-CGH assay based on Agilent technology and newly tested semi-conductive NGS technique (Torrent technology).